2023
DOI: 10.3390/ijms24087388
|View full text |Cite
|
Sign up to set email alerts
|

Persicae Semen Promotes Bone Union in Rat Fractures by Stimulating Osteoblastogenesis through BMP-2 and Wnt Signaling

Abstract: Fractures cause extreme pain to patients and impair movement, thereby significantly reducing their quality of life. However, in fracture patients, movement of the fracture site is restricted through application of a cast, and they are reliant on conservative treatment through calcium intake. Persicae semen (PS) is the dried mature seeds of Prunus persica (L.) Batsch, and in this study the effects of PS on osteoblast differentiation and bone union promotion were investigated. The osteoblast-differentiation-prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…PS facilitates mineralization and up-regulates Runx2 via BMP-2 and Wnt signaling pathways. Consequently, this leads to the expression of various osteoblast genes, including Alp , bone gamma-carboxyglutamate protein ( Bglap ), and integrin binding sialoprotein ( Ibsp ) 131 . Research has demonstrated that PS promotes fracture recovery by enhancing osteoblast differentiation and bone formation.…”
Section: Osteoblast Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…PS facilitates mineralization and up-regulates Runx2 via BMP-2 and Wnt signaling pathways. Consequently, this leads to the expression of various osteoblast genes, including Alp , bone gamma-carboxyglutamate protein ( Bglap ), and integrin binding sialoprotein ( Ibsp ) 131 . Research has demonstrated that PS promotes fracture recovery by enhancing osteoblast differentiation and bone formation.…”
Section: Osteoblast Signalingmentioning
confidence: 99%
“…Research has demonstrated that PS promotes fracture recovery by enhancing osteoblast differentiation and bone formation. Consequently, it could serve as a potential treatment option for patients with fractures 131 .…”
Section: Osteoblast Signalingmentioning
confidence: 99%
“…Activation of BMP-2 phosphorylates Smad and facilitates its translocation to the nucleus, activating p38 signaling. This, in turn, upregulates the expression of Runt-associated transcription factor 2 (RUNX2), which further promotes the process of fracture healing ( 88 ).…”
Section: The Role Of Primary Cilia In Bone Metabolismmentioning
confidence: 99%